2022
DOI: 10.3390/sports10020023
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intra-to-Extra-Cellular Water Ratio and Bioelectrical Parameters from Day-Before to Day-Of Competition in Bodybuilders: A Pilot Study

Abstract: The present study analyzed the effects from day-before to day-of bodybuilding competition on intracellular water (ICW), extracellular water (ECW), total body water (TBW), and bioimpedance analysis (BIA) parameters (resistance, R; reactance, Xc; and derived scores) in bodybuilding athletes. We assessed anthropometry and BIA (foot-to-hand; tetrapolar; 50 kHz) in 11 male bodybuilders (29 ± 4 year-old; 81 ± 8 kg; 172 ± 7 cm; 27 ± 2 kg/m2) both on the pre-competition day and on the contest day. Results revealed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…The outcomes observed throughout this investigation provide further insight to the physiological impacts to specific bodybuilding peaking strategies. Some of the data are supported by previous studies [ 5 , 6 , 11 ] while other results demonstrate novel findings that have not been formally examined to date. Previous research has shown that bodybuilders implement a variety of peaking strategies with the aim of enhancing body composition, maximizing muscle size, and minimizing the interstitial space/subcutaneous thickness [ 4 ]; however, the success rate and physiological impact of these strategies are not well established.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…The outcomes observed throughout this investigation provide further insight to the physiological impacts to specific bodybuilding peaking strategies. Some of the data are supported by previous studies [ 5 , 6 , 11 ] while other results demonstrate novel findings that have not been formally examined to date. Previous research has shown that bodybuilders implement a variety of peaking strategies with the aim of enhancing body composition, maximizing muscle size, and minimizing the interstitial space/subcutaneous thickness [ 4 ]; however, the success rate and physiological impact of these strategies are not well established.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, ~83% of the increases in TBW were estimated to be stored as ICW (+1.75 L), which improved the ratio between ICW and ECW from one day out (1.55) to competition morning (1.61). Although it is difficult to explain these favorable acute changes, recent data from a cohort of 11 male bodybuilders demonstrated similar results [ 6 ]. Nunes et al [ 6 ] demonstrated positive changes in ICW:ECW from one day out to competition day, however, they also observed reductions in TBW and ECW (which is what we hypothesized but did not observe).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations